An Analysis of Elle’s Personality as Reflected in Paul Weitz’s Film, Grandma (2015) - Leonora Gultom, Regina Sairum; Priyoto, Priyoto; Ramadhina, Retno (STIBA IEC JAKARTA, 2024)
The aim of this research is to analyze Elle's personality in the film “GRANDMA” as reflected in the film, focusing on the writer's detailed explanation using a psychological approach. The researcher collects data using a descriptive qualitative method based on the research problems. The researcher uses a psychological approach to analyze this film.To analyze this film the writer uses qualitative method. The data gathered is based on the results of seeing the film and categorizing the scenes and dialogue. The results showed that Elle's behavior in the film Grandma is influenced by the personality structure by the id structure. It is influenced by internal and external factors